Indirect additive manufacturing for patient-specific, highly complex medical devices (Transactions on Additive Manufacturing Meets Medicine, 2024)
Additive manufacturing enables the efficient production of highly complex components. In Binder Jetting, particle material is bonded in layers by selectively applying binder on particle layers. With this technique molds for metal casting, that can be applied in medical technology, can be produced in a cost-efficient way. The molds can be easily adapted, which is particularly interesting for patient-specific implants. In the work presented the stack casting and slurry-based binder jetting methods for the production of orthoses and joint implants will be discussed.An option for using indirect additive manufacturing in medical technology is stack casting, which can be used to produce larger, highly complex and individualized components for orthoses, for example. Here the casting mold is made up of several casting mold pieces. This way a higher design complexity and simplified automatization of cleaning can be reached [1]. The additional degrees of freedom provided by additive manufacturing enable new possibilities in the design of orthoses, which can lead to better handling for the patient.For more precise cast parts restrictive parameters such as surface roughness or mechanical stability can be improved by using slurry instead of powder, in the so-called slurry-based binder jetting [2]. Using this technology, it is feasible to vary and optimize the microstructure of the implant, by adjusting the wall thicknesses of the cast and the casting mold. This could lead to an improved performance of the implant and with this to better durability. Slurry-based binder jetting has the potential to produce mechanically stable, complex, and delicate molds for investment casting. This would be a more efficient way of producing investment casting components such as knee, hip and finger joint implants.
Keywords: indirect additive manufacturing; casting; patient specific implant